Entrapment of guidewire during central venous catheterization - S., Tarun; Nimaiyar, Harsh (International Journal of Research in Medical Sciences, 2017)
Central venous catheterization (CVC) is common in the setting of ICU for various reasons like monitoring of CVP, fluid administration and vasopressor or drug infusions. Guidewires are routinely used in the Seldinger technique during central venous catheter placement CVC placement is not innocuous as numerous complications may occur, with varying frequency and severity.